2013
DOI: 10.2337/db13-0813
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Neuropathic Pain in Diabetes by Targeting Glycosylation of Cav3.2 T-Type Calcium Channels

Abstract: It has been established that CaV3.2 T-type voltage-gated calcium channels (T-channels) play a key role in the sensitized (hyperexcitable) state of nociceptive sensory neurons (nociceptors) in response to hyperglycemia associated with diabetes, which in turn can be a basis for painful symptoms of peripheral diabetic neuropathy (PDN). Unfortunately, current treatment for painful PDN has been limited by nonspecific systemic drugs with significant side effects or potential for abuse. We studied in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 26 publications
6
94
0
1
Order By: Relevance
“…Although no mutations in Ca V 3.2 that result in increased pain in humans have been reported in the literature, peripheral nerve injury or inflammation (Jagodic et al, 2008;García-Caballero et al, 2014), diabetes (Jagodic et al, 2007;Messinger et al, 2009), and colonic inflammation (Marger et al, 2011a) all give rise to increased DRG neuron T-type calcium currents in rodents. At least two mechanisms appear to contribute to this phenomenon: an enhancement of Ca V 3.2 channel trafficking, due to glycosylation in the case of diabetic pain (Orestes et al, 2013;Weiss et al, 2013), and stabilization of these channels as a result of enhanced deubiquitination (García-Caballero et al, 2014). Inhibiting Ca V 3.2 channels pharmacologically thus mediates analgesia (François et al, 2014).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…Although no mutations in Ca V 3.2 that result in increased pain in humans have been reported in the literature, peripheral nerve injury or inflammation (Jagodic et al, 2008;García-Caballero et al, 2014), diabetes (Jagodic et al, 2007;Messinger et al, 2009), and colonic inflammation (Marger et al, 2011a) all give rise to increased DRG neuron T-type calcium currents in rodents. At least two mechanisms appear to contribute to this phenomenon: an enhancement of Ca V 3.2 channel trafficking, due to glycosylation in the case of diabetic pain (Orestes et al, 2013;Weiss et al, 2013), and stabilization of these channels as a result of enhanced deubiquitination (García-Caballero et al, 2014). Inhibiting Ca V 3.2 channels pharmacologically thus mediates analgesia (François et al, 2014).…”
Section: Ca V 3 Channel Pathophysiologymentioning
confidence: 99%
“…This aspect may have important implications in chronic disorders such as peripheral painful diabetic neuropathy where enhanced expression of T-type channels is believed to contribute to the development and maintenance of this condition [145][146][147][148]. This notion is further supported by the observation that peripheral injection of neuraminidase in an animal model of diabetes reversed neuropathic pain [143]. Altogether, these data indicate that N-glycosylation of Ca v 3.2 channels, in addition to influencing the gating properties of the channel [149], contributes to the maintenance of the channel protein in the plasma membrane, and may have important physiopathological implications.…”
Section: Asparagine-linked Glycosylationmentioning
confidence: 87%
“…However, it was only recently that the functional role of N-glycosylation in the trafficking of T-type channels was analysed. We and others have shown that glycosylation of Ca v 3.2 channels at specific loci is essential for surface expression of the channel protein [142,143]. For instance, disruption of the glycosylation loci at asparagine N192 and N1466 in the human Ca v 3.2 channel caused Although N-glycosylation of Ca v 3.2, especially at asparagine residues N192 and N1466 (in the human channel), has little influence on the forward trafficking to the cell surface, it enhances the life-time of the channel in the plasma membrane by slowing down its internalization.…”
Section: Asparagine-linked Glycosylationmentioning
confidence: 94%
“…Indeed, labeling of both channel protein and cell membrane did not show an overlap that was detectable at our resolution, suggesting that this channel was not properly inserted into cell membrane. Multiple structural elements of Ca V 3 channels contribute to surface expression of the channel protein: the middle and distal part of the I-II loop [13,24], III-IV loop [25,26], amino terminal region [27], and external glycosylation sites [28,29]. None of these sites seems to be able directly interact with the uppermost arginines in S4 segments.…”
Section: Discussionmentioning
confidence: 99%